2020
DOI: 10.3329/ptcb.v30i1.47794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of explants for in vitro propagation of Citrus indica Tanaka - An Endangered Species

Abstract: Of the five explants viz., shoot tip, nodal segment, leaf disc, cotyledon and root tip excised from exegenic seedlings of Citrus indica Tanaka shoot tip cultured in MS supplemented with 0.5 mg/l of BAP generated shoots within 4.74 days, exhibiting highest percentage of response (85.82%) with highest number of shoots (8.9) and shoot length (3.04 cm). On the other hand nodal segment cultured in MS supplemented with 1.0 mg/l BAP showed 80% response in 5.16 days with a shoot number of 5.41 and shoot length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Early root initiation and higher number of roots were achieved when 1 mg/l NAA was used in MS media. Similar observation was also reported by Sangma et al (2020), in Citrus indica. The combination of cytokinins did not show any significant improvement in root initiation.…”
Section: Chhetri Et Alsupporting
confidence: 91%
See 2 more Smart Citations
“…Early root initiation and higher number of roots were achieved when 1 mg/l NAA was used in MS media. Similar observation was also reported by Sangma et al (2020), in Citrus indica. The combination of cytokinins did not show any significant improvement in root initiation.…”
Section: Chhetri Et Alsupporting
confidence: 91%
“…The best treatments for achieving early shoot initiation, highest number of shoots per explant and longest shoots was found to be 0.5 mg/l BAP and 0.5 mg/l BAP + 1.0 mg/l Kn. Efficacy of 0.5 mg/l BAP was also reported by Sangma et al (2020) in a similar work carried out on micropropagation of Citrus indica. Although both the studies exhibited similar trend, the number of days required for shoot initiation and the mean number of shoots per explants varied significantly.…”
Section: Chhetri Et Alsupporting
confidence: 73%
See 1 more Smart Citation
“…with the ndings made byHamed et al (2007) in Jackfruit, who found the best results in MS medium out of B5 and WPM. The positive effect of full-strength MS medium over other media for axillary shoot proliferation was also studied previously in the Moraceae family, such as Ficus carica(Kumar et al,1998), Morus indica(Niratker et al, 2015) and Artocarpus lakoocha(Verma et al 2015), as well as in some other woody trees such as Lagerstromia parvi ora(Tiwari et al, 2002), Pterocarpus marsupium(Husain et al, 2008), Colutea istria (Hegazi and Gabr, 2010) and Citrus indica(Sangma et al, 2020).…”
mentioning
confidence: 61%
“…is based on T-budding 40-50 cm rootstocks with scion buds of specific cultivars, in an 18-24 months process to obtain plant material ready to plant in field crops, after mother plants have been carefully selected (Kamanga et al, 2017). Attempts to speed up the process include the use of tissue culture techniques such as rootstock production through micropropagation (Vashisth et al, 2020) and in vitro micrografting; however, low multiplication rates and time for ex vitro plantlet recovery are still a challenge (Chamandoosti, 2020;Sangma et al, 2020). The success of grafting is founded on a vascular reconnection between rootstock and scions, a process that involves hormones, molecular factors, and even whole genome transfer at the grafting area (Rasool et al, 2020;Gautier et al, 2019).…”
Section: ) Massive Propagation Of Citrus Plants For Cropsmentioning
confidence: 99%